Perancangan dan Pemodelan Basis Data untuk Sistem Informasi Manajemen Bengkel Mobil - Zaidan Prihantoro; Yohanes Hasiolan; Edwardus Imanuel; Zatin Niqotaini (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
The development of information technology currently demands efficiency in various industrial sectors, including automotive service businesses such as car repair shops. Most conventional workshops still rely on paper-based manual transaction recording for their daily operations. This unintegrated operational system often triggers major obstacles, such as the risk of losing physical receipts, inaccuracies in tracking spare part stock, and difficulties in compiling monthly revenue reports quickly. This study aims to build a database design model for a Car Workshop Management System capable of automating the business’s daily bookkeeping process. The research method used is descriptive qualitative, focusing on system development through a three-level structured database modeling approach. The results are outlined into three main diagrams: Entity Relationship Diagram (ERD), Conceptual Data Model (CDM), and Physical Data Model (PDM). The database structure is thoroughly designed by integrating admin and report entities, allowing the operational transaction data recapitulation process to generate revenue information automatically and instantly. The implementation of an intermediary table in the form of transaction details proves effective in preventing data redundancy. Overall, this database design is ready to be implemented on a DBMS to improve work efficiency and support workshop managerial decision-making.